PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS DAN LEVERAGE SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014 – 2017) - Eka Wulandini, 15.05.52.0007 Desi; Kartika, Andi (Students' Journal of Accounting and Banking, 2019)
This study aims to test and analyze the effect of Corporate Social Responsibility on Corporate Values with Profitability and Leverage as Moderating Variables. This research was conducted on the Indonesia Stock Exchange using a unit of analysis of manufacturing companies. The sampling method uses purposive sampling with the research period from 2014 to 2017. The influence of corporate social responsibility towards company value with profitability and leverage as moderation variables are accepted using the method Moderated Regression Analysis (MRA). The results of this study indicate that corporate social responsibility doesn’t effect the company value, but profitability and leverage can moderate the influence between CSR and company value.